Fluid-structure coupling analysis of a pressure vessel-pipe-safety valve system with experimental and numerical methods. (October 2022) - Zong, Chaoyong; Li, Qingye; Zheng, Fengjie; Chen, Dianjing; Li, Xiaofeng; Song, Xueguan
Abstract: Pressure vessel-pipe-safety valve (PVPSV) is a commonly used combination in the industrial pressure systems. For the design optimization purpose, an in-depth investigation on the working mechanism of such a combination is essential. To this end, experimental and numerical analysis were performed in this paper. For measuring, an experimental test rig is specially designed and built, thereby dynamic tests were performed. The results indicate that the set-pressure of the safety valve and the valve spring stiffness have significant influence on the dynamics of the PVPSV. Upon certain operating conditions, the safety valve responds in unstable manners, e.g., flutter or chatter. To compensate the tests, a high-fidelity 2-D axis-symmetric system-level Computational Fluid Dynamics (CFD) model is used. The simulation results show that both the damping coefficient and the connecting pipe length have great influence on the dynamics of the PVPSV system. A PVPSV system with a small damping coefficient and/or a long connecting pipe is more likely to exhibit dynamic instability. Finally, combining the results of experiments and numerical simulations, a large enough net disc force coupled with insufficient kinetic energy loss of valve moving parts are considered to be the root cause of unstable operations of the PVPSV system. Highlights: An test rig containing a vessel, pipe and a valve is developed, thereby FSI of the PVPSV system can be studied in depth. The FSI has a non-negligible influence on the dynamic response of the pressure vessel-pipe-safety valve system. A better combination of the disc force and damping could avoid undesirable vibrations of the safety valve/PVPSV system.